Sprawozdanie Komisji Historii Nauki PAU w 2017/2018 roku - Michał Kokowski (Studia Historiae Scientiarum)
The report discusses the activities of the Commission on the History of Science of the Polish Academy of Arts and Sciences in 2017/2018. It presents the lists of: scientific meetings, new members, new publications, and members who have died.